2006
DOI: 10.1308/003588406x98702
|View full text |Cite
|
Sign up to set email alerts
|

Ionising Radiation Exposure to Orthopaedic Trainees: The Effect of Sub-Specialty Training

Abstract: INTRODUCTION We monitored image intensifier use by orthopaedic trainees to assess their exposure to ionising radiation and to investigate the influence of sub-specialty training.MATERIALS AND METHODS Five different orthopaedic registrars recorded their monthly image intensifier screening times and exposure doses for all cases (trauma and elective), for a combined total of 12 non-consecutive months. Radiation exposure was monitored using shoulder and waist film badges worn both by surgeons and radiographers sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 23 publications
(24 reference statements)
2
23
0
3
Order By: Relevance
“…In the next step, only studies where effective radiation to the surgeon was directly measured in the operating theatre were further considered for this review. Studies using indirect measurements or formulas to back calculate surgeon exposure [14][15][16][17][18][19][20][21][22][23][24] as well as studies measuring radiation exposure in Gray only were not further reviewed because of the problem of comparability [25][26][27][28][29][30][31].…”
Section: Methodsmentioning
confidence: 99%
“…In the next step, only studies where effective radiation to the surgeon was directly measured in the operating theatre were further considered for this review. Studies using indirect measurements or formulas to back calculate surgeon exposure [14][15][16][17][18][19][20][21][22][23][24] as well as studies measuring radiation exposure in Gray only were not further reviewed because of the problem of comparability [25][26][27][28][29][30][31].…”
Section: Methodsmentioning
confidence: 99%
“…Effort should be to supplement image to the clinical knowledge and not vice versa [2]. Some studies have reported that more the experience lesser is the exposure [13,18].…”
Section: B Personnel Related Factorsmentioning
confidence: 99%
“…This is very difficult to implement in an in vivo study. For this reason, the radiation doses are typically measured with thermoluminescense dosimeters (TLDs) [9][10][11][12] . Hereby, the radiation is converted to light and consecutively measured.…”
Section: Resultsmentioning
confidence: 99%
“…In spine surgery, different studies showed a high exposure to radiation performing dorsal stabilisations on the spine 10 . The position of the radiation source is really important to reduce the scatter radiation as much as possible.…”
Section: Resultsmentioning
confidence: 99%